1988
DOI: 10.1111/j.1423-0410.1988.tb01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Lipid‐Enveloped Viruses in Labile Blood Derivatives by Unsaturated Fatty Acids

Abstract: Virus sterilization of blood plasma derivatives by addition of several naturally occurring fatty acids was evaluated using vesicular stomatitis virus and Sindbis virus as markers for lipid-enveloped virus inactivation and human immunodeficiency virus (HIV). Inactivation of greater than or equal to 10(4) tissue culture infectious doses (TCID50) of marker viruses added to antihemophilic factor (AHF) concentrates, with 60-100% retention of AHF activity, was achieved with oleic, 11-eicosenoic, linoleic, linolenic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This could indicate that a potential protective effect of DGLA on progression to severe dengue might be mediated through reduced inflammation. Another intriguing potential mechanism could be related to virucidal activity against encapsulated viruses that some longchain n-6 PUFA have shown in vitro (40)(41)(42)(43) . DGLA breastmilk concentrations were inversely related to cell-free and cellassociated HIV load in milk in a study of Tanzanian HIVinfected women (44) .…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate that a potential protective effect of DGLA on progression to severe dengue might be mediated through reduced inflammation. Another intriguing potential mechanism could be related to virucidal activity against encapsulated viruses that some longchain n-6 PUFA have shown in vitro (40)(41)(42)(43) . DGLA breastmilk concentrations were inversely related to cell-free and cellassociated HIV load in milk in a study of Tanzanian HIVinfected women (44) .…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids and fatty acid-containing molecules were found to inactivate enveloped viruses, HSV-1 included, by disintegrating the virus lipid envelope (Horowitz et al, 1988;Kohn et al, 1980;Thormar et al, 1987). On the other hand, Hilmarsson et al (2005) observed that the acidic environment makes HSV more sensitive to certain virucidal lipids (fatty alcohols and lipids), possibly by ionic changes in the envelope proteins.…”
Section: Discussionmentioning
confidence: 99%
“…HIV inactivation study was performed using a high-titered stock purchased from Bionetics Research Inc. (Kensington, Md., USA). PEG-precipitated samples were suspended in culture medium and added to lymphocytes cultures [39]. Supernatants were checked every 3 days for quantitation of HIV-P24Ag using the Abbott HIV EIA kit.…”
Section: Virus Studymentioning
confidence: 99%